First-Principles Calculations of Structural Properties of NaNbO 3 - Machado, Rodrigo (2012)
We present ab-initio total energy calculations for different structures of NaNbO3 at different volumes using two different exchange-correlation functionals: the Perdew and Wang version of the local-density approximation (LDA) and the Wu and Cohen version of the generalized gradient approximation (GGA-WC). We found that LDA not only underestimates the equilibrium volume of the system but also predicts an incorrect ground state for this oxide. The GGA-WC functional, on the other hand, significantly improves the equilibrium volume and provides a relative phase stability in better agreement with experiments. We then use the GGA to investigate the presence of structural instabilities as a function of volume in order to provide insights for the understanding of the structural behavior of K1-xNaxNbO3 solid solutions.